Transparent Power-Generating Windows Based on Solar-Thermal-Electric Conversion - Zhang, Qihao; Huang, Aibin; Ai, Xin; Liao, Jincheng; Song, Qingfeng; Reith, Heiko; Cao, Xun; Fang, Yueping; Schierning, Gabi; Nielsch, Kornelius; Bai, Shengqiang; Chen, Lidong (Advanced Energy Materials, 2021)
Integrating transparent solar-harvesting systems into windows can provide renewable on-site energy supply without altering building aesthetics or imposing further design constraints. Transparent photovoltaics have shown great potential, but the increased transparency comes at the expense of reduced power-conversion efficiency. Here, a new technology that overcomes this limitation by combining solar-thermal-electric conversion with a material's wavelength-selective absorption is presented. A wavelength-selective film consisting of Cs0.33WO3 and resin facilitates high visible-light transmittance (up to 88%) and outstanding ultraviolet and infrared absorbance, thereby converting absorbed light into heat without sacrificing transparency. A prototype that couples the film with thermoelectric power generation produces an extraordinary output voltage of ≈4 V within an area of 0.01 m2 exposed to sunshine. Further optimization design and experimental verification demonstrate high conversion efficiency comparable to state-of-the-art transparent photovoltaics, enriching the library of on-site energy-saving and transparent power generation.
CRIS-Team Scopus Importer:2022-04-14
Keywords: energy-saving; solar-thermal-electric conversion; thermoelectric devices; transparent power-generating windows; visible-light transmittance; wavelength-selective absorption